A Dual Nano-Signal Probe-Based Electrochemical Immunosensor for the Simultaneous Detection of Two Biomarkers in Gastric Cancer - Li-Ting Su; Zhen-Qing Yang; Hua-Ping Peng; Ai-Lin Liu (Biosensors)
Detecting multiple tumor markers is of great importance. It helps in early cancer detection, accurate diagnosis, and monitoring treatment. In this work, gold nanoparticles–toluidine blue–graphene oxide (AuNPs-TB–GO) and gold nanoparticles–carboxyl ferrocene–tungsten disulfide (AuNPs–FMC–WS2) nanocomposites were prepared for labeling Carcinoembryonic antigen (CEA) antibody and Carbohydrate antigen 72–4 (CA72-4) antibody, respectively, and used as two kinds of probes with different electrochemical signals. With the excellent magnetic performance of biotin immune magnetic beads (IMBs), the biofunctional IMBs were firmly deposited on the magnetic glassy carbon electrode (MGCE) surface by applying a constant magnetic field, and then the CEA and CA72-4 antibody were immobilized on the IMBs by the avidin–biotin conjugation. The assay was based on the change in the detection peak current. Under the optimum experimental conditions, the linear range of detection of CEA is of the two-component immunosensor is from 0.01 to 120 ng/mL, with a low detection limit of 0.003 ng/mL, and the linear range of detection of CA72-4 is from 0.05 to 35 U/mL, with a detection limit of 0.016 U/mL. The results showed that the proposed immunosensor enabled simultaneous monitoring of CEA and CA72-4 and exhibited good reproducibility, excellent high selectivity, and sensitivity. In particular, the proposed multiplexed immunoassay approach does not require sophisticated fabrication and is well-suited for high-throughput biosensing and application to other areas.